Hippocampal neurovascular and hypothalamic-pituitary-adrenal axis alterations in spontaneously type 2 diabetic GK rats - Beauquis, Juan (2010)
Metabolic and vascular consequences of diabetes mellitus induce several CNS complications. The dentate gyrus of the hippocampus, a well-recognized target for diabetic alterations, is a neurogenic area associated with memory and learning processes. Here, we explored the hippocampal neurogenesis and its microenvironment (astrocytes, vascularisation and glucocorticoid influence) in a spontaneous model of type 2 diabetes, the Goto-Kakizaki rat. The number of proliferative Ki67(+) cells and young doublecortin(+) neurons was 2-fold higher in the hippocampus from diabetic rats than in normoglycemic control Wistar at 4 months of age. However, there was no difference in cell survival, studied 3 weeks after bromodeoxyuridine administration. Labeling of endothelial cells against von Willebrand factor, demonstrated a 50% decrease in the granular cell layer fractional area covered by blood vessels and a diminished capillary branching in diabetic rats. Finally, Goto-Kakizaki rats exhibited decreased glucocorticoid receptor immunolabeling in CA1, associated with higher corticosteronemia. In conclusion, diabetic rats showed increased cell proliferation and neuronal differentiation without concomitant survival modification. A high proliferation rate, potentially reflecting a compensatory mechanism for neuronal suffering, also exists in various pathological situations. However, endothelial alteration induced by chronic hyperglycemia, hyperleptinemia and insulin resistance and associated with deleterious glucocorticoid effects might impair effective neurogenesis in diabetic Goto-Kakizaki rats.